Edukasi Penerapan Protokol Kesehatan Pada Era New Normal Sebagai Bentuk Upaya Pencegahan Pengendalian Covid-19 - Jayani, Indah; Ramayanti, Eva Dwi; Susmiati, Susmiati (Universitas Nusantara PGRI Kediri, 2021)
The Covid 19 pandemic has an impact on all sectors, especially the health sector. Public health is the main focus of government attention. One of the efforts that have been made is to break the chain of covid transmission by limiting activities outside the home and self-quarantine. After carrying out activities only at home, social and economic problems emerge, requiring people to return to carrying out activities to meet their daily needs. The new life order or the so-called new normal is an alternative for the government to solve these complex problems. The public is expected to implement health protocols in the new normal era as a form of efforts to prevent the transmission of covid 19. To achieve this goal the participation of health workers is highly expected. The role of education is the main thing that must be done considering that many people don't know, don't understand about the new normal and what health protocols must be done in the new normal era. Kediri City is one of the areas that is of concern to the East Java Provincial Government because even though it is in the yellow zone, it has a high risk of increasing its status because it is a reference city in the trade economy sector in the Kediri residency area. The updated data obtained from the Kediri City Office on 4 August 2020 obtained an additional 110 cases. One factor in the increase in cases is due to the tendency of people's attitudes and behavior to ignore health protocols. Therefore education is an urgent thing that must be done so that the public knows and understands how to live a new life while still paying attention to health protocols as a form of efforts to prevent COVID-19 transmission. The abdimas team in collaboration with Puskesmas Campurejo carries out community service to provide Health Protocol Education in the New Normal era in efforts to support the central government and local government programs of Kediri City. The key to the success of efforts to prevent the transmission of covid 19 is if the Government, Health Workers and all levels of society work together to comply with health protocols properly. For this reason, we, a team of health workers from the Faculty of Health Sciences, Kadiri University, have participated in efforts to realize government programs by providing education on health protocols in the new normal.